Improving Social Science Learning Outcomes through the Application of the Discovery Learning Model with e-LKPD Media for Grade IV Elementary School Students - Triwahyuningtyas, Dyah; Sari, Laili Ayu Arum; Setyaningsih, Yuyun (Actual Insight, 2025)
This research aims to improve the learning outcomes of Natural and Social Sciences (IPAS) students of grade IV C Sekolah Dasar Negeri 1 Bakalan Krajan Malang through the application of the Discovery Learning model assisted by e-LKPD media. The background of this study is the low learning outcomes and limited student engagement in IPAS learning, which is partly caused by conventional learning models and the absence of interactive digital teaching materials. This class action research (PTK) was carried out in two cycles following the Kemmis and McTaggart model, each consisting of planning, implementation, observation, and reflection stages. In cycle I, learning was conducted using the Discovery Learning model without integrating e-LKPD media, while in cycle II, the learning process was supplemented with the use of interactive e-LKPD, designed to guide students in discovery activities, problem-solving, and critical thinking tasks. The research subjects involved 28 students of grade IV C. Data collection was carried out through learning outcome evaluation tests conducted at the end of each cycle. The results of the study showed a significant increase in learning completeness, from 58% in the first cycle to 89% in the second cycle, indicating a 31% improvement. These findings prove that the application of the Discovery Learning model assisted by e-LKPD media is effective not only in enhancing students’ learning outcomes in IPAS but also in increasing active student participation, engagement, and motivation during the learning process.